Community Empowerment in Waste Management Household Using Barrel Media - Ichsan, Nursyamsi; Hasmiati Attas, Nasrah; Nasir, Citra (Cendekiawan Indonesia Timur, 2022)
Economic development in Palopo City continues to increase; this has implications for waste production, which increases significantly in quantity, quality, and complexity. The development of time is always accompanied by population growth, so automatically, the amount of waste generation increases and does not increase, even though the available land is challenging to find sufficient land for waste processing. This service activity aims to increase community knowledge about household waste management and empower the community to convert household waste into organic fertilizer. This service activity has been carried out with various achievements by the output targets, namely, socialization of household waste management through this activity is expected to increase knowledge about household waste management properly and training in the utilization of household waste into fertilizer products that can be used for themselves or sold to provide economic benefits.